GovSecure.ID: Inclusive and secure digital transformation strategy through AI-based adaptive multichannel architecture and public literacy towards efficient governance 2045 - Maulana Fabian Ardiman; Rasya Abhista Ar Rafi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Digital transformation in public governance demands secure, integrated, and accessible service systems to strengthen public trust and administrative efficiency. fragmented government platforms, limited transparency, and low accessibility remain persistent challenges in delivering inclusive public services. this study responds to these issues by proposing GovSecure.ID as a conceptual digital governance platform designed to integrate data security, public service access, and intelligent interaction within a single system architecture. Methods: This research employs a qualitative–conceptual design approach grounded in governance theory, digital government frameworks, and secure information system principles. data were obtained through literature review, policy document analysis, and conceptual system modeling. analytical procedures focused on synthesizing institutional requirements, user needs, and technological capabilities to construct an application framework, interface logic, and feature mapping. No empirical testing or field implementation was conducted, positioning the study as design-oriented exploratory research. Findings: The study produces a structured conceptual model of the GovSecure.ID application, consisting of integrated digital identity services, transparent fiscal information access, disaster reporting mechanisms, and an ai-based conversational assistant (govbot). visualization of the login page, main interface, and ai interaction demonstrates how digital services can be centralized while maintaining clarity, accessibility, and institutional accountability. findings indicate strong potential for improving service responsiveness, data transparency, and citizen engagement within a secure governance environment. Conclusion: GovSecure.ID conceptually demonstrates how intelligent systems can support public service delivery without replacing formal administrative authority. the proposed model emphasizes security, inclusivity, and responsiveness as foundational principles for future digital governance platforms in indonesia. Novelty/Originality of this article: This article contributes originality by integrating artificial intelligence, secure digital identity, and transparency-oriented governance within a single conceptual platform framework, offering a scalable reference model for future government digital service development.